2021
DOI: 10.1089/pmr.2021.0005
|View full text |Cite
|
Sign up to set email alerts
|

Care Provider Behaviors That Shape Parent Identity as a “Good Parent” to Their Seriously Ill Child

Abstract: Background: Parents of medically complex children hold deeply personal definitions of how to be ''good parents'' that guide their medical decision making and interactions with providers and are impacted by provider behaviors.Objective: This study explored whether and how these beliefs are shaped by interactions with care providers and which provider behaviors foster or impede parents' ability to achieve their ''good parent'' definitions. Methods: A 63-item web-based survey distributed by an online support netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This involves acknowledging the importance parents place on their role and tailoring care plans to align with the values and beliefs of each family. However, HCPs should also be careful not to contribute to unrealistically high expectations on parents, as research has shown that interactions with HCPs impact parents’ definitions of what a good parent is [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This involves acknowledging the importance parents place on their role and tailoring care plans to align with the values and beliefs of each family. However, HCPs should also be careful not to contribute to unrealistically high expectations on parents, as research has shown that interactions with HCPs impact parents’ definitions of what a good parent is [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, parents could be overwhelmed with responsibility when compelled to perform tasks with which they are not comfortable. Both circumstances threaten the parent's own conceptualization of what it means to be a “good parent,” their own personal framework of beliefs that guide their coping and decision‐making, which often includes elements such as keeping their child safe, preventing pain, and advocating effectively (Hinds et al, 2009 ; Neumann et al, 2021 ; Weaver et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of good parent beliefs includes making informed unselfish decisions in the best interest of the child; providing the basics of food, shelter and clothing; remaining at the child's side; showing the child that it is cherished; trying to prevent suffering and protect health; teaching the child to make good choices; advocating for the child with the staff; and promoting the child's health (Hinds et al, 2009;Weaver, October, Feudtner & Hinds, 2020). Beliefs serve as an identity to parents, forming an ideal and an internal compass that guides medical decisions concerning their child (Neumann, Weaver, Lord, Wiener, & Hinds, 2021). Parents differ and construct their own understanding of what being a good parent implies (Weaver et al, 2020) Moreover, parental beliefs are personal and may shift or develop over time, influenced by parent-clinician interactions (Weaver, Hinds, Kellas, & Hecht, 2021).…”
Section: Good Parent Beliefsmentioning
confidence: 99%